Mentorship Experiences and Perceptions of Didactic Program in Dietetics Students. Issue 1 (January 2021) - Patten, Emily Vaterlaus; Bellini, Sarah Gunnell; Meier, Amanda; Earl, Kaitlin
Abstract : This study explored dietetics students' experiences and perceptions of mentoring. A survey was developed, piloted, and then distributed to dietetics students in the United States. Descriptive statistics were calculated, and open-ended data were analyzed using a conventional line-by-line content analysis approach. Students (n = 611) representing 69 dietetics programs completed the survey. Most (58%) cited a "professor or instructor" as their mentor, and only 20% reported no mentor. Themes that emerged from open-ended responses are the mentor, the process, and relationship expectations. Mentoring perceptions and experiences of students can guide educators and practitioners in supporting the pipeline of professionals.